El ciclo del aprendizaje y su aplicación en la planificación micro-curricular de 4°, 5° y 6° años de educación básica de la escuela Dr. Luis Felipe Chávez del cantón Latacunga provincia de Cotopaxi en el periodo lectivo 2015 - 2016 - Bautista Tello, Mayra Elizabeth (2016)
The objective of this research was: "Design a micro-curriculum planning guide aimed to the teachers of 4th, 5th and 6th years of basic education of Dr. Luis Felipe Chavez School. The reason for this research was: "How the learning cycle is used by the teacher in the micro-curricular planning and execution." The methodological design corresponds to the quantitative method because it was developed by tables and graphs; descriptive level that the characteristics of the problem was detailed and field type because it was made in an educational institution and bibliographic because the information was taken from written sources. The results of the research were: "The learning cycle is not evidence on the block or in the class properly; curriculum planning blocks in most of the cases are transcribing digital or printed documents, changing some data. The contribution of this work was: "The development of a guide for designing a Micro-curricular Planning with Learning Cycle Application.